THE ROLE OF RELIGIOUS EDUCATION TEACHERS IN SHAPING THE PROFILE OF PANCASILA STUDENTS - Muthoharoh Muthoharoh (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
Teachers are the spearhead of student outcomes; by optimizing their functions and roles, they can form a nation with Pancasila character. This study aims to describe and analyze the role of Islamic Religious Educationeachers in shaping Pancasila students profile.The research location is MI Ma'arif Pranggong Indramayu. This is a qualitative study, and the data is presented in a descriptive format. Teachers and students participated in this study. Observation, interviews, and documentation were used to collect data. According to the findings of the research the role of PAI teachers as educators, role models, motivators, mentors, facilitators, and evaluators played a role in shaping Pancasila Students who had faith, noble character, liked to work together, were independent, and creative. Students' character development is carried out through a variety of activities, including learning, extracurricular activities, religious activities, and clean Friday activities. Following up on these findings, optimizing the role of teachers both in and out of the classroom is a concern in nurturing students and creating a generation of Pancasila characters.